Pengaruh Asma terhadap Kehamilan (Literature review) - Salsabila Iatiqfanisa; Rahayu Kusuma Candrakirana; Winda Aenah; Manggala Pasca Wardhana (Universitas Batanghari Jambi, 2023)
Asthma is a chronic disease that complicates pregnancy. For pregnant women with comorbid asthma, things will be much more difficult during their pregnancy. Seeing the increasing prevalence of asthma in the community, the incidence of asthma in pregnancy will be more common. The effects of asthma in pregnancy are varied and unpredictable and vice versa. Several studies have shown that asthma has an impact during pregnancy and pregnancy can affect changes in the clinical status of asthma patients and even the fetus in the womb. This study aims to find out how asthma affects pregnancy. This study used a literature review study design. Research article searches were sourced from the Pubmed, Google Scholar, and Scopus electronic databases. Search articles using keywords, namely asthma, pregnancy, lung function. The results of a review of three journals that have been conducted show that hormonal changes, lung function and function, and uterine anatomy of pregnant women will affect the recurrence and control of asthma. However, the degree of influence of asthma in pregnancy varies according to the variation. But the effect of asthma on pregnancy will result in premature birth, young gestational age, hypertension in pregnancy, placental abruption, and cesarean section. The data we reviewed can be concluded that there is an effect of asthma on pregnancy resulting in premature birth, early gestational, hypertension in pregnancy, placental abruption, and cesarean section.